1986
DOI: 10.1111/j.1464-410x.1986.tb05920.x
|View full text |Cite
|
Sign up to set email alerts
|

Vas Cannulation with Implanted Sperm Reservoirs for Obstructive Azoospermia or Ejaculatory Failure

Abstract: Seven patients with azoospermia due to obstruction of the abdominal part of the vas deferens, and five paraplegic men with ejaculatory failure, were treated with implanted sperm reservoirs. In eight patients (67%) motile spermatozoa were recovered. Two pregnancies (17%) were achieved with subsequent live births (by AIH). In two patients the fertilising capacity of the spermatozoa was unsuccessful as assessed by IVF. Infection required the removal of two reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 5 publications
0
14
0
4
Order By: Relevance
“…Another group of investigators have found normal levels of noradrenalin in the corpora cavernosa of men with SCI (Melman et al, 1980). Thus, according to Brindley et al (1986), the sympathetic system appears to have both erectile and anti-erectile actions (particularly the latter action). The regulation of these opposing actions and their integration with the parasympathetic activity is still under investigation (Brown et al, 2006).…”
Section: Erectionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another group of investigators have found normal levels of noradrenalin in the corpora cavernosa of men with SCI (Melman et al, 1980). Thus, according to Brindley et al (1986), the sympathetic system appears to have both erectile and anti-erectile actions (particularly the latter action). The regulation of these opposing actions and their integration with the parasympathetic activity is still under investigation (Brown et al, 2006).…”
Section: Erectionmentioning
confidence: 94%
“…In previous studies some investigators have suggested that the semen analysis in spinal cord injured men, in the chronic phase, demonstrates low (Perkash et al, 1985) to normal (Momen et al, 2007) sperm count and low sperm motility (Perkash et al, 1985;Brindley et al, 1986;Brackett et al, 1995). In the international literature there is limited data on human semen characteristics in the acute phase after SCI.…”
Section: Sperm Parameters After Scimentioning
confidence: 96%
“…Because of lack of success, we now apply Brindley's sperm reservoir. 19 The reservoir is ā at container with non-pierceable bottom; implanted directly in the lumen of the vas deferens by a small tube. After subcutaneous implantation, it can be punctured percutaneously and semen can be withdrawn.…”
Section: Surgical Methodsmentioning
confidence: 99%
“…The vasa deferentia are cannulated in the inguinal canal, and the reservoirs are sited under the deep fascia of the anterior abdominal wall just above and lateral to the internal inguinal ring. The reservoir has a self-sealing membrane in front to allow repeated needle puncture, and a rigid back plate and rigid side walls (Brindley et al 1986). When spermatozoa are required for insemination, the reservoir is punctured, the aspirate is discarded, and an equal volume (usually about 0.5 ml) of buffered tissue culture medium such as Earle's solution is instilled into the reservoir.…”
Section: Sperm Reservoirsmentioning
confidence: 99%